Gliadin activates mucosal cell mediated immunity in cultured rectal mucosa from coeliac patients and a subset of their siblings. Issue 4 (1st October 1998) - Troncone, R; Mazzarella, G; Leone, N; Mayer, M; De Vincenzi, M; Greco, L; Auricchio, S
Abstract : Background —CD3 and γδ cells in the rectal mucosa increase after local instillation of gluten in children with coeliac disease and in half of their siblings. Aim —To establish an in vitro system for assessing immunological changes induced by gluten in the rectum. Patients and Methods —Rectal biopsy specimens obtained from 13 treated coeliac children, nine of their siblings, and nine controls were cultured in vitro with a peptic-tryptic digest of gliadin or ovalbumin. CD3 and CD25 cells were counted, and the expression of adhesion molecules evaluated. Results —In the lamina propria of coeliac biopsy samples cultured with gliadin, but not in those from controls, the expression of vascular cell adhesion molecule 1 (VCAM-1) was enhanced, and the number of CD25 cells was significantly higher than in those cultured in medium alone; the density of intraepithelial CD3 cells was also significantly higher. No differences were noted in coeliac biopsy specimens cultured with ovalbumin. A discriminant analysis allowed correct classification of all controls and all coeliacs but one, but three of nine siblings were allocated to the coeliac group. Conclusions —Our data confirm that gliadin is able to activate cell mediated immunity in the rectal mucosa in coeliac patients and in a subset of their first degree relatives.